Sulphated dehydroepiandrosterone serum levels are reduced in women with alcohol use disorder and correlate negatively with craving: A sex-separated cross-sectional and longitudinal study - Weinland, Christian; Mühle, Christiane; von Zimmermann, Claudia; Kornhuber, Johannes; Lenz, Bernd (Addiction Biology, 2022)
Previous studies have established a role of sex hormones in alcohol use disorder (AUD).Only few clinical investigations with low numbers of patients with AUD have focused on the sulphated form of dehydroepiandrosterone (DHEA-S), despite its function as a neuromodulating sex steroid on receptors in the central nervous system (γ-aminobutyric acid type A, N-methyl-D-aspartate, sigma-1 receptors). DHEA-S serum levels were compared between 200 inpatients with AUD (44% women) admitted for withdrawal treatment and 240 healthy controls (45% women) and analysed longitudinally in patients from early abstinence (baseline) to a median of 5 days later. We also correlated DHEA-S levels with craving, liver enzyme activities, and prospective alcohol-related readmissions during a 24-month follow-up. DHEA-S concentrations were lower in female patients than in female healthy controls during baseline (70%) and decreased from baseline to follow-up in the female and male patients groups (down to: women, 92%; men, 76%). Baseline DHEA-S concentrations correlated with the total and obsessive subscales of the Obsessive–Compulsive Drinking Scale and with maximum visual analogue scale craving scores in female patients (Rho ≤ −0.240) and gamma-glutamyl transferase activity in female (Rho = −0.292) and male (Rho = −0.391) patients. DHEA-S did not significantly predict outcome. We found interactions with smoking behaviour and age. This is the first study based on large cohorts of inpatients with AUD undergoing a qualified detoxification treatment to provide sex-separated evidence for associations of DHEA-S serum concentrations with AUD and related phenotypes. The results stimulate further investigations whether DHEA-S directly influences alcohol craving building a basis to develop sex-sensitive prevention and treatment strategies.
CRIS-Team Scopus Importer:2022-03-11
Keywords: AUD; craving; DHEA -S; relapse; sex hormones